Effect of saliva contamination on microleakage of alkasite restorative material (Annals of Medical Research, 2022)
Aim: The aim of this study was to evaluate the effect of saliva contamination on the microleakage of resin composite, high-viscosity glass ionomer cement, and an alkasite restorative material.Materials and Methods: Eighty class II cavities were prepared on the mesial and distal surfaces of 40 extracted human molar teeth. Teeth were divided into four restorative material groups [resin composite (Solare X, GC), glass ionomer cement (Fuji IX GP, GC), an alkasite restorative material with and without adhesive (Cention N, Ivoclar Vivadent)] and mesial cavities were contaminated with human saliva (n=10). Restorative materials were applied and after the setting time of materials, restorations were finished. Specimens were thermo-aged, and were subsequently immersed in 0.5% methylene blue dye solution. Teeth were sectioned through the center of the restorations in mesio-distal direction. The extent of dye penetration was assessed using a stereomicroscope. The data was analyzed using the Kruskal-Wallis and Wilcoxon nonparametric tests (p˂0.05)Results: Among the non-contaminated and saliva contaminated groups Fuji IXGP (FGP) showed the highest microleakage scores (p˂0.05). Cention N with adhesive showed the least microleakage, the difference between the alkasite groups and Solare X was not significant (p˃0.05). Both of the Cention N groups showed a lower microleakage when contaminated by saliva than FGP (p˂0.05). Saliva contamination significantly increased the microleakage scores of all groups except FGP (p˂0.05).Conclusions: An alkasite restorative material applied with or without adhesive revealed lower microleakage than high-viscosity glass ionomer cement in both non-contaminated and saliva contaminated groups.
Keywords: Composite resins; glass ionomer cements; Cention N; saliva; dental leakage